Cymbidium shidianense (Orchidaceae: Epidendroideae), a new species from China: evidence from morphology and molecular data - Chen, Gui-Zhen; Zhang, Guo-Qiang; Huang, Jie; Wang, Meng; Rao, Wen-Hui; Chen, Li-Jun (Phytotaxa, 2019)
A new orchid species, Cymbidium shidianense (Orchidaceae; Cymbidieae), from Yunnan Province, China, is described and illustrated based on morphological and molecular analyses. This new species is similar in morphology to C. cyperifolium, but it differs in its larger pseudobulbs, rigid leaves, broader pale green sepals, petals with darkly coloured veins and set of V-shaped blotches on the lip midlobe. A phylogenetic analyses based on nuclear ribosomal ITS and plastid (matK, rbcL) DNA sequence data support C. shidianense as related to C. cyperifolium.